(untitled) (International Journal of Environmental Sciences, 2025)
The digital era has brought about paradigm shifts in postgraduate education delivery, causing serious challenges for students, especially where university services are ill-equipped to meet their learning and research needs. Following the narrow and broad literature review approach, this desktop study conducted a comprehensive review of literature focused on structures and support services that universities provide to meet postgraduate students’ learning and research needs. The findings reveal different support structures and services that enable postgraduate students navigate their learning and research programmes with successes, namely: academic libraries, funding, Information and Communication Technology (ICT), and dedicated academic support services. However, as the learning and research environments become increasingly complex, universities need to improve their structures and support services to make them more relevant to postgraduate students learning and research needs for better academic experiences. This study provides critical information relevant for benchmarking any university’s structures and services against similar best practices.